THE URGENCY OF TRAINING IN IMPROVING EMPLOYEE PERFORMANCE - Hanayanti, Sevi; Ikhawan , Khairul (Sekolah tinggi ilmu ekonomi pemuda, 2022)
This study aims to provide an overview of the development of research on employee training and performance. This type of research uses a qualitative approach where the source of data is used in this study is secondary data. Secondary data is data obtained in the form of documents and written reading materials that have a close relationship with the problems discussed. Meanwhile, in the data collection method, the author uses library research or literature studies. The sample of this research is articles published in 12 nationally accredited journals for 8 years of observation from 2013 to 2020. The sample used is 14 articles that discuss employee training and performance. This study classifies articles based on the dependent, independent, and moderating variables. The most researched topic is from the dependent variable is employee performance, the most studied independent variable is training. The results of this study are the independent variable training dominates this training by 27 percent, and the dependent variable in this study that dominates the employee performance by 56 percent.